Agronomic performance and fruit sensory and quality analyses of pineapple cultivars - Freitas, Angélica Padilha de; Krause, Willian; Arantes, Debora Sarana Ortolan; Castro Silva, Dayane; Santos, Eileen Azevedo; Campos , Renê Arnoux da Silva (Comunicata Scientiae, 2024)
The objective of this study was to assess the agronomic performance and fruit sensory and quality characteristics in traditional and modern pineapple cultivars grown in Tangara da Serra, MT, Brazil. The experiment was conducted in a randomized block design, with five replications and 20 plants per plot. Planting was carried out in double rows with spacing of 1.2×0.4×0.4 m, in May 2018. The evaluated cultivars were BRS-Ajuba, BRS-Imperial, BRS-Vitoria, Gigante-de-Tarauaca, IAC-Fantastico, Jupi, Perola, and Smooth-Cayenne. Gigante-de-Tarauaca exhibited the highest fruit weight but presented low soluble solids content and soluble solids to titratable acidity ratio (SS/TA); thus, it is not recommended for fresh fruit market. Jupi exhibited fruit weights (>1500 g) suitable for the market and soluble solids above 12 °Brix, but SS/TA below 20. Considering the modern cultivars, BRS-Ajuba presented the highest fruit weight, but BRS-Imperial and IAC-Fantastico were the most attractive to consumers, as well as the traditional cultivar Perola. However, BRS-Imperial and IAC-Fantastico yield small fruits, which reduces their per-unit value in the market, as pineapples are typically valued based on their sizes.